(untitled) (Canadian Journal of Emergency Management, 2023)
Is your organization ready to survive and exploit the opportunities that arise in every crisis? Disasters are increasing in scale, scope, and complexity and the structures currently in place are not designed to handle the now-common ‘disaster within a disaster’. The COVID-19 pandemic has shown us that our current systems need revision and updating. Black Swan events—the exceedingly rare and highly disruptive events that can trigger existential crises for organizations and societies (Taleb, 2010)—once seen as generational events are now commonplace, interrelated, and compounding components of daily life (Kayyem, 2022; Marcus et al., 2019; Roux-Dufort, 2007). Despite this reality, the reactive design of many humanitarian and disaster response organizations leaves them vulnerable during major events thus at risk of being unable to fulfil their mandates. The mantras “it cannot happen here” and “it will not happen again” are naïve and dangerous.